The administration of Islamic justice: position and jurisdiction of syariah court in Malaysia - Wan Muhammad, Ramizah (2020)
Malaysia operates a dual legal system: Common/Civil law and the Islamic legal system. The common law system is a legacy of British colonialism, 1824-1957. The Shari‘ah based system is Islamic in which Islamic law is implemented in the country. The Supreme law in Malaysia is the Federal Constitution of Malaysia, which was created right after Malaysia gained independence in 1957. The constitution is the supreme law of the land in which all laws created in Malaysia, Islamic or civil law, must conform to the federal constitution. This paper discusses the position and roles of the Syariah Court in Malaysia as an Islamic institution in safeguarding the faith of the Muslims and upholding Islamic law as the basis of justice. The history of Syariah Court as one of the oldest institutions in the legal history in Malaysia is also highlighted so that one could see the original position of the court prior to the colonisation and after the colonisation. It is equally important to look at the jurisdiction of Syariah Courts in Malaysia which is divided into civil and criminal jurisdiction. This information is significant to see the extent of the application of Islamic criminal law in Malaysia, as a modern Muslim state. There are also other Islamic institutions or agencies, which are significant in the administration of Islamic justice such as enforcement division, prosecution department and Department of Syariah Judiciary Malaysia (JKSM).